Time to presumptive conceptus attachment and subsequent pregnancy loss in pasture-based lactating dairy cows following artificial insemination with conventional or X-sorted semen or embryo transfer - A.D. Crowe; J.M. Sánchez; S.G. Moore; M. McDonald; F. Randi; A. Santos; T. Minela; J. Branen; J. Furlong; J.R. Pursley; P. Lonergan; S.T. Butler (Journal of Dairy Science)
ABSTRACT: The objective of this study was to determine the effect of the timing of presumptive conceptus attachment (pCA) and its relationship with subsequent pregnancy loss (PL) in lactating dairy cows following timed artificial insemination with conventional (TAI-C) or X-sorted (TAI-S) semen or timed embryo transfer (TET) with frozen-thawed in vitro–produced (IVP) embryos. Lactating cows (n = 417, predominantly Holstein-Friesian) located in 3 herds were blocked based on parity, calving date, and economic breeding index and randomly assigned to receive TAI-C (n = 136), TAI-S (n = 136) or TET with a single, grade-1 frozen-thawed IVP blastocyst (n = 145). Cows were synchronized with a 10-d Progesterone-Ovsynch protocol, and were either inseminated (TAI-C, TAI-S) 16 h after the second GnRH or received TET on d 7 after presumptive estrus. Serum progesterone was measured in all cows on d 7 after expected ovulation. For all cows that had not returned to estrus, serum pregnancy-specific protein B (PSPB) was measured on d 7, 17, and daily from d 19 through 28 after expected ovulation to characterize the timing of pCA. The day of pCA was defined as the first day of an increase in PSPB of ≥12.5% from baseline (d 17) followed by 2 more consecutive days of ≥12.5% increase from the previous day. Pregnancy was diagnosed in cows that had not returned to estrus via ultrasound examination on d 32, 62, and 120 postovulation, and calving data were recorded. Day of pCA (mean; 95% CI) was earlier for TAI-C (20.0; 19.7, 20.3) compared with TET (20.6; 20.3, 20.9), and TAI-S (20.3; 19.9, 20.6) was not different from the other 2 treatments. Calving/service event (C/SE) was greater (83.2% vs. 54.4%) and PL during the interval from pCA to expected calving date was less (16.8% vs. 45.6%) for cows with early pCA (≤d 20; 23/137) compared with cows that had late pCA (≥d 21; 36/79). The incidence of PL was greater for cows assigned to TAI-S (30.7%) and TET (33.8%) than TAI-C (16.4%). Consistent with previous studies, measuring time to pCA provides new insights into understanding early pregnancy establishment and PL in lactating dairy cows. The timing of pCA was later for TET compared with TAI-C and may be associated with increased risk of PL. Further research into the regulatory mechanisms underlying conceptus attachment is warranted.